INFEKSI SALURAN KEMIH AKIBAT PENGGUNAAN KATETER PADA PASIEN RAWAT INAP DI RUMAH SAKIT - Ananta, Yoga; Mustofa, Syazili; Septiani, Linda; Busman, Hendri (CV. Jasa Sukses Abadi, 2025)
Urinary tract infection (UTI) is a disorder caused by microorganisms that multiply in the urinary tract, which is normally sterile from bacteria. Risk factors for UTI include age, gender, medical procedures such as catheterization, hygiene, and duration of catheter use. Catheter-related UTI is the most common type of nosocomial infection, with a prevalence of up to 80% in patients who use catheters. The main cause of UTI is gram-negative bacteria, such as Escherichia coli (48.44%) and Klebsiella pneumoniae. In women, the risk is higher because the urethra is shorter and closer to the anus. UTI is divided into lower and upper urinary tract infections, where symptoms vary from pain during urination to serious complications such as pyelonephritis and urosepsis. The pathophysiology of UTI often involves the colonization of microorganisms on the catheter or urinary tract. The risk of infection increases with the duration of catheter placement, reaching 5–10% per day. Diagnosis of UTI involves history taking, physical examination, and urine culture, although modern methods such as flow cytometry are increasingly used for efficiency. Prevention involves personal hygiene, aseptic technique during catheter insertion, and prophylactic antibiotic use in selected cases. Treatment of UTI includes empiric antibiotics such as trimethoprim-sulfamethoxazole, fluoroquinolones, or nitrofurantoin, depending on the severity and causal pathogen. Appropriate preventive and treatment approaches can reduce the incidence of UTI, improve patient quality of life, and decrease the rate of complications. Keywords: Trigger Factors, Urinary Tract Infection (UTI), Catheter